2020
DOI: 10.3390/ijerph17176295
|View full text |Cite
|
Sign up to set email alerts
|

What Protective Health Measures Are Americans Taking in Response to COVID-19? Results from the COVID Impact Survey

Abstract: With the emergence of the novel SARS-CoV-2 and the disease it causes; COVID-19, compliance with/adherence to protective measures is needed. Information is needed on which measures are, or are not, being undertaken. Data collected from the COVID Impact Survey, conducted by the non-partisan and objective research organization NORC at the University of Chicago on April, May, and June of 2020, were analyzed through weighted Quasi-Poisson regression modeling to determine the association of demographics, socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 37 publications
8
35
1
1
Order By: Relevance
“…In Punjab 71.8% participants were always wearing a mask when going outside, 91.8% participants were followed the stay at home policy, 53.8% participants were followed the steps of hand hygiene [ 43 ]. Based on an impact survey done America, about 94.7% of participants reported washing or sanitizing hands, 39.6% reported working from home, and 9.6% reported visiting a doctor or hospital [ 44 ]. Survey of Bangladish showed that, more than half 51.6% of respondents had good practices of COVID 19 preventive measure [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Punjab 71.8% participants were always wearing a mask when going outside, 91.8% participants were followed the stay at home policy, 53.8% participants were followed the steps of hand hygiene [ 43 ]. Based on an impact survey done America, about 94.7% of participants reported washing or sanitizing hands, 39.6% reported working from home, and 9.6% reported visiting a doctor or hospital [ 44 ]. Survey of Bangladish showed that, more than half 51.6% of respondents had good practices of COVID 19 preventive measure [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of these preventive measures could be linked to greater trust placed in government/authorities, as verified in Seale et al (2020) [ 43 ]. In fact, Qeadan et al (2020) have already verified that the group of older people acquired more measures established by the competent authorities [ 44 ]. Therefore, authorities should consider the impact of their instructions and guidance, especially with respect to the group over 60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, existing literature suggests that the adoption of such preventive measures is generally low, and there exist substantial variations across countries and regions. [7][8][9] The underlying reasons why people do or do not choose to practice recommended preventive measures have not been well-characterized. This knowledge gap has hindered efforts to effectively control the transmission of COVID-19.…”
Section: Introductionmentioning
confidence: 99%